AVALIAÇÃO QUANTITATIVA DO DESLOCAMENTO ESPACIAL DO ZÊNITE GENGIVAL NA DENTIÇÃO ANTERIOR DA MAXILA - Mattos, Carolina Miller Leite de (2008)
The appearance of the gingival tissues plays an important role in the aesthetics of the anterior maxillary region of the mouth. The gingival zenith (GZ) is defined as the most apical point of the marginal gingival scallop, however its quantitative orientation in the apico-coronal (AC) and mesio-distal (MD) directions have not been previously reported. Thus, this study aimed to quantify the specific spatial displacement of the GZ in the maxillary anterior dentition. Measurements performed in maxillary stone casts from periodontally-healthy volunteers with a digital caliper were recorded to the nearest 1/100 of the millimeter, bilaterally, in the canine (C), lateral (LI) and central incisor (CI) teeth, in order to evaluate the MD displacement of the GZ in relation to the long axis of the crowns and the AC displacement of the GZ of the LI in relation to the CI and C. Inter-measurements differences were analyzed with a Chi-square or a paired t-test, with significance set at α<0.05. The GZ was distally-displaced, between 0.08 mm and 0.96 mm, in 12% (C), 70% (LI) and 96% (CI) of the teeth. The majority of the population (70%) presented with the GZ of the lateral incisor positioned 0.75 ± 0.60 mm coronally to the GZ of the ipsi-lateral C and CI. The gingival zenith is not universally displaced towards the distal. The frequency and magnitude of distal displacement is tooth-dependent and larger in CI than in the LI, which, in turn, is larger than in the C. Consideration to these findings may improve clinical management of the dento-gingival complex and enhance periodontal and restorative procedures in the anterior maxillary dentition.